2018
DOI: 10.3390/nano8070519
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Nanosheets in Frontier Cellular Research

Abstract: Several types of nanosheets, such as graphene oxide (GO) nanosheet, molybdenum disulfide (MoS2) and poly(l-lactic acid) (PLLA) nanosheets, have been developed and applied in vitro in cellular research over the past decade. Scientists have used nanosheet properties, such as ease of modification and flexibility, to develop new cell/protein sensing/imaging techniques and achieve regulation of specific cell functions. This review is divided into three main parts based on the application being examined: nanosheets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 124 publications
(175 reference statements)
0
18
0
Order By: Relevance
“…The induced alteration of cells’ proliferative potential was demanded as one of the most possible modes of many 2D materials’ action. According to our best knowledge, there is still a lack of fundamental information on the influence of MXenes on cellular cycle and DNA synthesis. To face this issue, we carried out studies on cellular death type, which also confirmed the results of MTT assay (time- and dose-dependent cytotoxicity of examined nanostructures).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The induced alteration of cells’ proliferative potential was demanded as one of the most possible modes of many 2D materials’ action. According to our best knowledge, there is still a lack of fundamental information on the influence of MXenes on cellular cycle and DNA synthesis. To face this issue, we carried out studies on cellular death type, which also confirmed the results of MTT assay (time- and dose-dependent cytotoxicity of examined nanostructures).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The enhanced cytotoxic and apoptotic activity of the biogenic sulfur can be attributed to the many advantages of the 2D nanosheet morphology such as the large specific surface area for cell adhesion and internalization, abundance of sulfur atoms in ultrathin nanosheets, high capability of release of sulfur atoms, high polarized charges, and convenient attachment of different functional groups. 30,31 A study by Loutfy et al on the cytotoxic effect of graphene oxide nanosheets toward HepG2 cancer cells has shown that the cytotoxic effect was due to the strong interaction with the phospholipid layer leading to internalization into mitochondria, nucleus, and cytoplasm, causing membrane integrity loss and damage. 62 Further, SNP-B exhibited higher cytotoxic effects against cancer cell lines while showing minimum toxicity to normal cells compared to SNP-C.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Studies have proved that cells can internalize nanosheets, resulting in a higher interaction between the substrate and cells . Internalization and cellular distribution will have a direct impact on the cytotoxicity of the nanosheets . In the present study, sulfur nanosheets have shown a higher cytotoxicity compared to sulfur nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, nanosheets have been incorporated into a broad range of biosensor applications. [283] The high SA/V ratio allows for increased interaction between the sensor surface and analytes of interest. [284] Additionally, the 2D confinement of electrons in these materials can yield unique optical and electrical properties.…”
Section: Nanosheetsmentioning
confidence: 99%